Memory in mind and culture - Boyer, Pascal; Wertsch, James V. (Cambridge University Press, 2009)
This text introduces students, scholars, and interested educated readers to the issues of human memory broadly considered, encompassing both individual memory, collective remembering by societies, and the construction of history. The book is organised around several major questions: How do memories construct our past? How do we build shared collective memories? How does memory shape history? This volume presents a special perspective, emphasising the role of memory processes in the construction of self-identity, of shared cultural norms and concepts, and of historical awareness. Although the results are fairly new and the techniques suitably modern, the vision itself is of course related to the work of such precursors as Frederic Bartlett and Aleksandr Luria, who in very different ways represent the starting point of a serious psychology of human culture.